Politeness In The Digital Spotlight: Analyzing Language Use In Deddy Corbuzier's 'close The Door' Podcast - Helmaliya, Erisa Putri; Andarwulan, Trisna; Panich, Pensri (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2024)
Language plays a crucial role in social communication, including on digital platforms such as YouTube. One of the most popular podcasts in Indonesia, "Close The Door" by Deddy Corbuzier, often showcases various forms of adherence to and violations of linguistic politeness. This study aims to describe the forms of adherence to and violations of politeness in the podcast using a cyberpragmatic perspective. The data source for this research is the video podcast "Close The Door," featuring a dialogue between Ivan Gunawan and Deddy Corbuzier titled "Cowo Kok Tas Cewe." This study employs a qualitative descriptive method, with data collection techniques conducted through documentation, observation, and note-taking. The data analysis procedure follows the stages outlined by Miles, Huberman, and Saldana, which include data collection, data condensation, data presentation, and conclusion drawing. Additionally, data triangulation in this study is based on sources, techniques, and time. The results indicate that violations of politeness in the podcast often take the form of jokes that lack respect for conversation partners and the use of vulgar language, reflecting a lack of attention to linguistic politeness.